"Northwest trail" - Abrahams, Derwin, 1903-1974; Gates, Harvey H., 1889-1948; Steele, Bob, 1907-1988; Woodbury, Joan, 1915-1989; Curwood, James Oliver, 1878-1927.; Action Pictures; Cinetel Films ([Los Angeles, CA] : Action Pictures, Inc., 1945)
Mountie Matt O'Brien is assigned to escort Miss Owens to a remote outpost. But when he finds an illegal mining operation there that is smuggling gold across the border, his superior Sgt. Means orders him to leave. --
Originally released as a motion picture in 1945.
Based on James Oliver Curwood characters.
Bob Steele, Joan Woodbury, John Litel, Raymond Hatton.
Cinematographer, Marcel Le Picard; editor, Tom Neff; music, Frank Sanucci.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 15, 2016).
Keywords: Mounted police -- Drama; Gold smuggling -- Drama; Western films; Film adaptations; Feature films; Internet videos; Streaming video